Double diaphragm forming simulation for complex composite structures. (April 2017) - Chen, S.; McGregor, O.P.L.; Endruweit, A.; Elsmore, M.T.; De Focatiis, D.S.A.; Harper, L.T.; Warrior, N.A.
Abstract: A finite element (FE) model has been developed to simulate the double diaphragm forming (DDF) process, to identify potential defects when forming complex 3D preforms from 2D biaxial non-crimp fabric plies. Three different metrics have been introduced to predict and characterise defects, which include local shear angles to determine ply wrinkling induced by over-shear, compressive strains in the primary fibre directions to determine bundle wrinkling, and tensile stresses in the primary fibre directions to determine fabric bridging. The FE simulation is in good agreement with experiments performed on a demonstrator component. Results indicate that fabric bridging occurs in large-curvature regions, which is the dominant defect in DDF, as wrinkling is generally lower than in matched-tool forming due to relatively low forming pressures (up to 1 bar). The axial tensile stress in fibres has been used as a measure to identify suitable positions and orientations for darts, to alleviate fabric bridging and improve surface conformity, whilst minimising the effect on the mechanical performance of the component.